RESPONS PERILAKU BULU BABI Deadema setosum TERHADAP LOGAM BERAT KADMIUM - Rumahlatu, Dominggus (Bumi Lestari, 2012)
Deadema setosum are sea urchins which are very sensitive to heavy metal pollutants. In this research, the observation of behavioral responses namely the behavior of moving and resting Deadema setosumare conducted. They are caused by exposure of different heavy metals Cd at 4 agurium tanks for 4 weeks. Analysis of levels of heavy metals Cd that accumulates in the gonad and intestine Deadema setosum using Atomic Absorbsion Spectrofotometer (AAS). The observations shows responses of switching behavior and resting Deadema setosum that fluctuats during 4 weeks of observation. In addition, behavioral end point’s observations about the losing of spines is not observed during these 4 weeks. The content levels of Cd which accumulates in the intestine and the gonads increase from the first tank (lowest value) to the fourth tank (the highest), the result show that tanks 1 <2 <3 <4. The results of these observations indicate that the behavior of moving and resting Deadema setosum influenced by heavy metal concentrations of Cd that accumulates in the body of Deadema setosumwhich occurs through a process of absorption.
Keywords: behavioral responses; behavioral end point’s; Deadema setosum; heavy metal cadmium